2006
DOI: 10.1002/app.24743
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the shear flow on a homogeneous polymeric reaction

Abstract: The reaction kinetics of the postamidation of polyamide 6 in the melt was studied by a new rheological method, and the reaction rate constant was calculated to be about 0.087 kg/mol min at 2508C. To study the effects of the shear flow on a homogeneous polymeric reaction, a more practical technique was used to select the data that responded only to the reaction without the effect of different shear flows. The experimental results showed that the reaction rate constant decreased with an increase in the shear rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…This suggests that dynamic shear can promote the coupling reaction when the initial interface has only a low coverage of block copolymer. However, the dramatic viscosity increase reported by Kim et al and Xie et al was not observed for the PS/PMMA bilayer, as discussed in the Appendix. , …”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…This suggests that dynamic shear can promote the coupling reaction when the initial interface has only a low coverage of block copolymer. However, the dramatic viscosity increase reported by Kim et al and Xie et al was not observed for the PS/PMMA bilayer, as discussed in the Appendix. , …”
Section: Resultsmentioning
confidence: 88%
“…SM640 was also sheared dynamically under various conditions, with frequencies ranging from 0.05 to 10 rad/s and strain amplitudes from 0.05 to 15%. The reaction conversion did not change significantly. , Kim et al and Xie et al reported that dynamic shear could have significant effects on coupling reactions. , However, the samples used in their studies were laminated rather than extruded, and little reaction happened during the lamination process. Therefore, we speculate that the minimal reaction observed with SM640 under dynamic shear was due to the interface already being highly covered with block copolymer.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations